2016
DOI: 10.1172/jci85676
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Gpr45 causes reduced hypothalamic POMC expression and obesity

Abstract: SZ helped analyze the screen data. XW conceived of and designed the studies, supervised the work, and wrote the manuscript. YW and LX performed the electrophysiology studies. MZ and WJ performed the hyperinsulinemic-euglycemic clamp analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 85 publications
1
17
0
1
Order By: Relevance
“…Our findings showed that the aged miR‐188 null mice had an unchanged food intake (Figure g); however, their oxygen (O 2 ) consumption and energy expenditure (EE) were significantly higher compared with those of their WT littermates (Figure h–i), which suggested that the decreased body fat mass of the aged miR‐188 null mice was largely the result of increased energy expenditure. Under a normal environmental temperature, energy expenditure mainly comprises thermogenesis and physiological activities (Cui et al, ). Although their physiological activities were not changed (Figure m,n), the aged miR‐188 null mice had a significantly higher body temperature than their WT littermates (Figure o).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings showed that the aged miR‐188 null mice had an unchanged food intake (Figure g); however, their oxygen (O 2 ) consumption and energy expenditure (EE) were significantly higher compared with those of their WT littermates (Figure h–i), which suggested that the decreased body fat mass of the aged miR‐188 null mice was largely the result of increased energy expenditure. Under a normal environmental temperature, energy expenditure mainly comprises thermogenesis and physiological activities (Cui et al, ). Although their physiological activities were not changed (Figure m,n), the aged miR‐188 null mice had a significantly higher body temperature than their WT littermates (Figure o).…”
Section: Resultsmentioning
confidence: 99%
“…In the aged miR‐188 null mice and aged adipose tissue‐specific miR‐188 transgenic mice, the food intake was unchanged; however, the oxygen consumption and energy expenditure were significantly increased or decreased compared with those in the corresponding control mice, respectively. Under normal environmental conditions, energy expenditure occurs through physiological activities and thermogenesis (Cui et al, ; Deng et al, ; Wyler, Lord, Lee, Elmquist, & Liu, ). The mice's physiological activities were unchanged; however, the expression of thermogenesis‐related genes increased or decreased significantly in the BAT and iWAT of aged miR‐188 null mice or aged adipose tissue‐specific miR‐188 transgenic mice, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We have identified a Vkorc1l1 mutant through a forward genetic screen for obesity‐related loci in mice . In this report, we show that disruption of Vkorc1l1 leads to defective adipogenesis associated with increased vitamin K 2 in preadipocytes.…”
Section: Introductionmentioning
confidence: 70%
“…Based on the data obtained from our growth retardation screen and previously reported ENU screens (7,8), we estimate that our engineered transposon is 5-fold more potent than ENU in its ability to induce functional mutations (SI Appendix, Table S2). Moreover, we previously conducted a PB insertional recessive screen for obesity (21). We recorded the body weight of all animals in the obesity screen and have now analyzed the original data from the screen for growth retardation.…”
Section: Discussionmentioning
confidence: 99%
“…A Pilot PB F1 Dominant Screen for Growth Retardation. We have previously used both ES-based knockout technology and the PBbased F3 recessive screening system in mice to study mechanisms underlying body size control (20,21). To evaluate the power of our F1 screening system, we conducted a pilot screen for a growth retardation phenotype, an important phenotype that serves as an indicator of many systematic defects: 2,036 F1 animals were screened before weaning age and compared to their wild-type siblings from the same litter.…”
Section: Development Of a Highly Efficient F1 Mutagenesis Screening Smentioning
confidence: 99%